At This Point in the Game (GESTIÓN Y TENDENCIAS, 2018)
A tax system should be as understandable and as simple as possible for any actor in the national economy, and above all in a business world that lies not only within Chile's borders but beyond them. Far more important, however, is that the tax rules should not undergo significant changes of interpretation during the implementation phase of a reform.